Pengaruh keteladanan dan pola asuh orangtua terhadap egosentrisme anak usia dini - Syafrina, Rizqi; Brantasari, Mahkamah; Ardiana, Reni; Ika Pratiwi, Yuni Ika Pratiwi; Risela Echaristy, Auditia; Meyssi, Monika (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2025)
This study aims to analyze the influence of parental role modeling and parenting styles on egocentrism in early childhood. The age of 4–6 years is considered a golden age, serving as a critical foundation for personality and character development, where parents play a central role in shaping children’s social behavior. This research employed a quantitative method with a survey approach. The participants were 177 parents of children aged 4–6 years. Data were collected using a Likert-scale questionnaire and analyzed through Spearman’s correlation test, as the data were not normally distributed. The findings indicate that parental role modeling has a significant relationship with children’s egocentrism; the higher the level of role modeling, the lower the tendency of egocentric behavior. Parenting styles also showed a significant relationship, although the effect was weaker than that of role modeling. Furthermore, a positive correlation was found between parental role modeling and parenting styles. Among the parenting styles, the democratic approach was identified as the most influential in reducing egocentric tendencies in early childhood. In conclusion, this study emphasizes the importance of parental role modeling and parenting styles in minimizing egocentrism during early childhood. Providing consistent positive role models and applying democratic parenting can effectively foster healthier social attitudes in children.